Templated grain growth of Bi(Zn0.5Zr0.5)O3 modified BiScO3−PbTiO3 piezoelectric ceramics for high temperature applications. Issue 3 (3rd July 2021) - Akça, Erdem; Duran, Cihangir; Kowalski, Ben; Sehirlioglu, Alp
ABSTRACT: 2.5Bi(Zn0.5 Zr0.5 )O3 −37.5BiScO3 −60PbTiO3 (BZZ-BS-PT) ceramics were successfully textured in the [001] by templated grain growth (TGG) process using 5 vol% <001>-oriented BaTiO3 (BT) plate-like templates. The templates were aligned in the matrix powder via tape casting and textured BZZ-BS-PT ceramics sintered at 1100°C for 3 h in air had a relative density of 98% and a Lotgering factor of 0.91. Chemically stable BT templates in Pb and Bi-rich BZZ-BS-PT system gave rise to the formation of highly oriented polycrystalline structure with larger block-like grains. A very high unipolar strain of 0.3% and low-field (<5 kV/cm) piezoelectric charge coefficient (d33 ) of 930 pm/V when driven at 50 kV/cm were achieved in highly textured ceramics together with a Curie temperature ( T C ) of 403°C. The TGG approach significantly improved piezoelectric properties of the BZ-BS-PT ceramic system without deteriorating the dielectric properties, which is a very promising high-performance candidate for high-temperature sensor, transducer and actuator applications.